Fossilized soft tissues in a Silurian platyceratid gastropod. - Sutton, MD; Briggs, D; Siveter, D; Siveter, D (2006)
Gastropod shells are common in the fossil record, but their fossil soft tissues are almost unknown, and have not been reported previously from the Palaeozoic. Here, we describe a Silurian (approx. 425 Myr) platyceratid gastropod from the Herefordshire Lagerstätte that preserves the oldest soft tissues yet reported from an undoubted crown-group mollusc. The digestive system is preserved in detail, and morphological data on the gonads, digestive gland, pedal muscle, radula, mouth and foot are also available. The specimen is preserved three-dimensionally, and has been reconstructed digitally following serial grinding. Platyceratids are often found attached to echinoderms, and have been interpreted as either commensal coprophages or kleptoparasites. The new data provide support for an attached mode of life, and are suggestive of a coprophagous feeding strategy. The affinities of the platyceratids are uncertain; they have been compared to both the patellogastropods and the neritopsines. Analysis of the new material suggests that a patellogastropod affinity is the more plausible of these hypotheses.